A versatile graphene foil. Issue 28 (29th June 2017) - Cui, L. F.; Wang, X. P.; Chen, N.; Zhang, G. F.; Qu, L. T.
Abstract : Graphene foil with high electrical conductivity exhibits versatile features, as a flame-retardant material and a substitute for metal current collectors. Abstract : Free-standing graphene is extremely attractive for a range of applications due to its light-weight and unique structure when the low electrical conductivity and availability are well addressed. We herein prepared microscale-thick graphene foil (GF) via simple chemical vapor deposition on nickel foil. Unlike the self-supporting graphene films reported previously, this distinctive free-standing GF integrated with light weight, less defects, and outstanding electrical conductivity (4149 S cm −1 ) exhibits versatile features for various applications. The GF achieves excellent flame-retardant performance with a high decomposition temperature and can also be used as a perfect substitute for metal current collectors to replace the commercial metal foil in highly stable, lightweight lithium-ion batteries. The GFs provide a new material platform to further expand the practical applications of graphene in a variety of fields.